Catch per unit effort (CPUE) and population dynamics of hardtail scad (Megalaspis cordyla) at coastal area of Sungai Besar, Selangor - Mazlan, Muhammad Azri Zulfadhli (2013)
In Malaysia, carangid group of fishes contribute to large amount of marine fish capture and Megalaspis cordyla is one of them. The exploitation of the fish lately has given impact to the natural stock of the fish. The objectives of this study are to know the population dynamic of Megalaspis cordyla that was captured at coastal area of Sungai Besar, Kuala Selangor, Selangor and to know the catch per unit effort (CPUE) that the fisherman uses to catch the fish. Survey and collecting sample data of Megalaspis cordyla were done at Pengkalan Jeti Pendaratan Ikan Sungai Besar, Kuala Selangor, Selangor. Samples were collected once every month from January 2013 to October 2013. The total length (tl) in centimeter (cm) and the weight in gram (g) of each individual was taken and measured. Then the data had been analyses by using FiSAT. The population parameters, asymptotic length (L∞) in cm and growth co-efficient (K/year) are 41.48 and 0.430 respectively. Natural mortality (M/year), the fishing mortality (F/year) and total mortality (Z/year) are 0.9534, 1.8346, and 2.788 respectively. The exploitation level (E), was 0.658. The recruitment pattern of Megalaspis cordyla was continuous throughout the year and the major peak was during July- August. The length-weight equation calculated was W= 0.0151TL2.9017 (r2=0.9544). The CPUE for the fish are 0.0001875 kg h-1 L-1. These result shows unbalance position in the stock and indicate that Megalaspis cordyla in that area was over exploited.